2022
DOI: 10.1002/bse.3318
|View full text |Cite
|
Sign up to set email alerts
|

Green practices as an effective business strategy to influence the behavior of hotel guests in the luxury hotel sector: Evidence from an emerging market

Abstract: Researchers have investigated the influence of green practices on consumer behavior in the last decades. However, findings indicate that consumers have different responses toward green practices. To advance the current literature, this study draws on the theoretical foundation of social identity theory to investigate the relationship between green practices and hotel guests' visit intention in the luxury hotel sector. The study also determines the mediating mechanisms of perceived value fit and promotion focus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 82 publications
(215 reference statements)
1
4
0
Order By: Relevance
“…On the other hand, increased concern for the environment at work may also prompt employees and guests to adopt environmentally friendly behaviours at home. Moreover, research by Dang-Van et al [ 64 ] shows that green hotel practices increase the intention to visit a hotel, which is consistent with results from qualitative research on the focus group.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…On the other hand, increased concern for the environment at work may also prompt employees and guests to adopt environmentally friendly behaviours at home. Moreover, research by Dang-Van et al [ 64 ] shows that green hotel practices increase the intention to visit a hotel, which is consistent with results from qualitative research on the focus group.…”
Section: Resultssupporting
confidence: 75%
“…However, there are numerous efforts to ensure business sustainability [ 5 , 62 , 63 ]. Using sustainable practices has led many accommodation facilities to comply with environmental legislation [ 41 ] and apply elements of the bioeconomy, environmental management system, and social responsibility beyond legislation in their operations [ 21 , 64 ]. Understanding responsible visitor behaviour is essential for tourism entrepreneurs, especially in the accommodation sector, if they expect economic and environmental benefits [ 65 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Looking at the longer run, Mattioli et al (2020) suggested that we need to have a system of provision approach in cardependent societies. Nonetheless, future research shall explore other variables that might be mediating/moderating the subjective norms on the purchase intention of EVs as mentioned by Dang- Van et al (2023) that green practices and consumer outcomes are complex concepts to study.…”
Section: Discussionmentioning
confidence: 99%
“…SIT underlines that a part of individuals' self‐concept is related to their affiliation with social groups, including their present or future organisations (Jones et al, 2017). According to this theory, positive perceptions of organisations will reflect favourably on the employees within it, who get positive outcomes from other individuals (Dang‐Van et al, 2022; Wayne & Casper, 2012).…”
Section: Research Framework and Hypothesesmentioning
confidence: 99%